Deciphering transcriptional and functional heterogeneity in hematopoiesis with single-cell genomics - Martin-Rufino, Jorge D. (Curr Opin Hematol, 2021)
PURPOSE OF REVIEW: Single-cell genomic approaches have uncovered cell fate biases and heterogeneity within hematopoietic subpopulations. However, standard single-cell transcriptomics suffers from high sampling noise, which particularly skews the distribution of lowly expressed genes, such as transcription factors. This might preclude the identification of rare transcripts that define cell identity and demarcate cell fate biases. Moreover, these studies need to go hand in hand with relevant functional assays to ensure that observed gene expression changes represent biologically meaningful alterations. RECENT FINDINGS: Single-cell lineage tracing and functional validation studies have uncovered cell fate bias within transcriptionally distinct hematopoietic stem and progenitor subpopulations. Novel markers identified using these strategies have been proposed to prospectively isolate functionally distinct subpopulations, including long-term hematopoietic stem cells for ex vivo applications. Furthermore, the continuous nature of hematopoiesis has prompted the study of the relationship between stochastic transcriptional noise in hematopoietic transcription factors and cell fate determination. SUMMARY: An understanding of the limitations of single-cell genomic approaches and follow-up functional assays is critical to discern the technical and biological contribution of noise in hematopoietic heterogeneity, to identify rare gene expression states, and to uncover functionally distinct subpopulations within hematopoiesis.